One-part eco-cellular concrete for the precast industry: Functional features and life cycle assessment - Font, Alba; Soriano, Lourdes; Tashima, Mauro M. [UNESP]; Monzó, José; Borrachero, María Victoria; Payá, Jordi (Elsevier, 2020)
This paper focuses on investigating greener alternatives of cellular concrete technology to fulfil current searches for a shift to circular economy. A novel one-part eco-cellular concrete (ECC-OP) was developed and studied. The one-part alkali activated materials (AAM-OP) and new alkali-activated cellular concrete (AACC) technologies were combined to develop greener alternative of cellular concrete production. The progressive steps from traditional cellular concrete (TCC) based on ordinary Portland cement (OPC) and commercial aluminium powder (A) to a 100% waste-based cellular concrete are presented. Blast furnace slag (BFS) was the precursor, RHA was employed as the silica source, olive stone biomass ash (OBA) was the alkali source and recycled aluminium foil (AR) was employed as an aerating agent. The functional features of the materials were studied and compared to those established by the European standard and the American Concrete Institute (ACI) Committee 523 guides. The new ECC-OP with a bulk density, compressive strength and thermal conductivity that respectively equal 660 kg/m3, 6.3 MPa and 0.20 W/mK was obtained. Finally, a cradle-to-gate life cycle assessment (LCA) was made, where the industrial process of a masonry unit manufacture was raised by using each studied material. A 96% reduction in the kgCO2eq per m3 of material was reached with the new proposed ECC-OP compared to TCC manufacturing.
Keywords: Biomass ash; Blast furnace slag; Cellular concrete; CO2 emissions; Life cycle assessment; One-part alkali-activated material